Water consumption and distribution of dengue larvae in Pattani villages - A Luemoh; D McNeil; M Kuning (Journal of Health Science and Medical Research (JHSMR), 2003)
The water consumption characteristics and larval density of dengue haemorrhagic fever (DHF) vectors in DHF transmission and non-DHF transmission villages, as well as the relationship between these factors were investigated. We carried out a stratified cross-sectional survey during October and November 1998 in 160 households selected by randomized stratification from eight villages of Pattani province in southern Thailand. The villages were stratified by seaside or mountainside location, predominant religion of residents (Buddhist or Muslim), and transmission or non-transmission of dengue haemorrhagic fever. The mosquito larvae presence in containers used for storing drinking and washing water and the characteristics of these containers were measured. We used Mantel-Haenszel adjusted odds ratio and logistic regression to evaluate the factors determining DHF transmission in the village and the presence of larvae in the water containers. The larvae indices of dengue vectors were higher in the DHF transmission villages. There were strong associations between the water container characteristics, which varied between villages, and the presence of larvae. In particular, plastic containers were less likely to contain larvae.